Dysregulation of gut microbiota stimulates NETs-driven HCC intrahepatic metastasis: therapeutic implications of healthy faecal microbiota transplantation - Zhe Deng; Si Mei; Zhaoguang Ouyang; Ruoyu Wang; Lihuai Wang; Bo Zou; Jingjing Dai; Kexin Mao; Qian Li; Qianqian Guo; Chun Yi; Fanying Meng; et al. (Gut Microbes)
The stringent regulation of intrahepatic metastases is essential for improving survival outcomes in patients with hepatocellular carcinoma (HCC). This study investigated the impact of gut microbiota on intrahepatic metastasis of HCC and evaluated the therapeutic potential of healthy fecal microbiota transplantation (FMT). Dysregulation of the gut microbiota, characterized by a significant reduction in the abundance of beneficial bacteria, such as Anaerotruncus colihominis and Dysosmobacter welbionis, was observed in patients with intrahepatic metastatic HCC. A human flora-associated (HFA) intrahepatic metastatic HCC mouse model was successfully established through consecutive 4 weeks of human-mouse FMT. Dysregulation of gut microbiota promoted intrahepatic metastasis in the mouse model, primarily by enhancing neutrophil-mediated inflammatory responses and lead to excessive formation of neutrophil extracellular traps (NETs). Consequently, it promoted tumor vascular growth and tissue necrosis, resulting in intrahepatic metastasis of HCC. Notably, FMT from healthy donors mitigated these pathological processes. This study elucidated the role and mechanism of dysregulated gut microbiota in promoting intrahepatic metastasis of HCC. Healthy FMT emerges as a promising novel therapeutic strategy for preventing and treating intrahepatic metastasis of HCC.